The costal skeleton of the Regourdou 1 Neandertal. Issue 130 (May 2019) - Gómez-Olivencia, Asier; Holliday, Trenton; Madelaine, Stéphane; Couture-Veschambre, Christine; Maureille, Bruno
Abstract: The morphology and size of the Neandertal thorax is a subject of growing interest due to its link to general aspects of body size and shape, including physiological aspects related to bioenergetics and activity budgets. However, the number of well-preserved adult Neandertal costal remains is still low. The recent finding of new additional costal remains from the Regourdou 1 (R1) skeleton has rendered this skeleton as one of the most complete Neandertal costal skeletons with a minimum of 18 ribs represented, five of which are complete or virtually complete. Here we describe for the first time all the rib remains from R1 and compare them to a large modern Euroamerican male sample as well as to other published Neandertal individuals. The costal skeleton of this individual shows significant metric and morphological differences from our modern human male comparative sample. The perceived differences include: dorsoventrally large 1st and 2nd ribs, 3rd ribs with a very closed dorsal curvature and large maximum diameters at the posterior angle, a large tubercle-iliocostal line distance in the 4th rib, thick shafts at the dorsal end of its 6th ribs, thick mid-shafts of the 8th ribs, large articular tubercles at the 9th ribs, and thick shafts of the 11th and 12th ribs. Here we also describe a new mesosternal fragment: the left lateral half of sternebral segments 4 and 5. This portion reveals that the mesosternum of R1 had a sternal foramen in its inferiormost preserved sternal segment and supports previous estimation of the total length of this mesosternum. The new costal remains from R1 support the view that Neandertals, when compared with modern humans, show a significantly different thorax, consistent with differences found in other anatomical regions such as the vertebral column and pelvis.